Experimental observation of conditional past-future correlations - Yu, Shang (2019)
Conditional past-future correlations measure the lack of statistical independence between past and future system measurement outcomes when conditioned to a given state at a present time. Quantum non-Markovian memory effects are present whenever this correlation is not null. Conditional past-future correlations can also be used to detect initial system-environment correlated states. In this work, we provide theoretical and experimental evidence for these general properties. We build an optical setup that implements the dynamics of a qubit interacting with a dephasing spin bath. Both finite and infinite bath-size limits are observed. Confirmation of theoretical predictions for conditional past-future correlations is obtained. This work provides experimental support for quantum memory indicators based solely on outcomes of explicit system measurement processes.